Virtual mono-energetic images and iterative image reconstruction: abdominal vessel imaging in the era of spectral detector CT. Issue 8 (August 2020) - Al-Baldawi, Y.; Große Hokamp, N.; Haneder, S.; Steinhauser, S.; Püsken, M.; Persigehl, T.; Maintz, D.; Wybranski, C.
Abstract : AIM: To compare the quality of virtual mono-energetic (VMI) and polychromatic images reconstructed with hybrid iterative (PCIHIR ) or model-based reconstruction (PCIMBR ) derived from dual-layer spectral detector computed tomography (SDCT) in arterial phase images to visualise the aorta and abdominal main branches. MATERIAL AND METHODS: A retrospective review of 50 patients with abdominal arterial phase scans was undertaken. Attenuation, intraluminal noise, and signal-/contrast-to-noise ratio (S-/CNR) were assessed in the PCIHIR, PCIMBR and VMI40keV, VMI70keV, and VMI100keV images. Contrast, noise, and visualization of soft-plaque, and macro-/micro-calcifications were scored in a blinded reading by two radiologists. RESULTS: VMI40keV yielded highest S-/CNR ( p ≤0.001). VMI70keV and PCIMBR showed comparable SNR ( p ≥0.999) and yielded higher SNR than PCIHIR . VMI70keV yielded higher CNR than PCIHIR ( p <0.001) and PCIMBR ( p <0.045). VMI100keV yielded lowest CNR (p≤0.001) and SNR ( p ≥0.104). In the subjective analysis, VMI40keV outperformed PCIMBR for contrast and noise, PCIMBR scored better than VMI70keV, and the latter scored better than PCIHIR for these categories (all p <0.001). PCIMBR was superior for depiction of soft-plaque and micro-calcifications ( p <0.001). VMI100keV visualized micro-calcifications second best ( p <0.001) and matched PCIMBR for the depiction of macro-calcifications (p>0.999), while VMI40keV scored second best for depiction of soft-plaque ( p <0.020). CONCLUSIONS: VMI40keV and VMI70keV yield better S-/CNR than PCIHIR and PCIMBR ; however, PCIMBR visualized arteriosclerotic plaques best, followed by VMI40keV for depiction of soft-plaque and VMI100keV for macro- and micro-calcification. Based on the present findings, PCIMBR on conventional CT and VMI40keV supplemented by VMI100keV on SDCT are recommended for the diagnostic assessment of abdominal arteries. Highlights: Model-based iterative reconstructions visualize arteriosclerosis best. Virtual mono-energetic images at 40 keV show soft-plaque second best. Virtual mono-energetic images at 100 keV show calcification second best. VMI at 40 and 70 keV improve objective image quality over polychromatic images.